Total Microbial Analysis of School Snacks (PJAS) in Junior High School Canteens in Kendari - Purwantari, Herni; Djaila, Sri Rizki (Journal of Food and Agricultural Product, 2025)
Food safety for school children's snacks (PJAS) in Indonesia remains a concern because consumption of PJAS in Indonesia is relatively high, contributing significantly to the daily energy intake of school children. According to data from the Indonesian Food and Drug Administration (BPOM) on schools participating in the PJAS food safety improvement program, 7,7% of PJAS products still fail to meet microbiological permissible standards. Among the microorganisms detected in these PJAS products, there is a high likelihood that pathogenic organisms capable of causing various health issues, including vomiting, dizziness, diarrhea, and even death, are present. Data from the Kendari City Health Department in 2022 shows that diarrhea is the primary infectious disease. The study aimed to determine the total microorganisms in PJAS at junior high school canteens in Kendari City using a multistage cluster sampling technique. Six canteens were randomly selected from six districts in Kendari City. At each canteen, one sample was taken from each PJAS category based on BPOM classification, namely colored beverages, agar-agar, ice, noodles, light meals, meatballs, and snacks. The total microbiological contamination in PJAS was analyzed using the Total Plate Count (TPC) method. Among 28 PJAS samples collected from six junior high school canteens in Kendari City, two exceeded the maximum permissible total microbial threshold. These samples belonged to the colored beverage category, with total microbes of 3.7x10^4 CFU/ml and 1.2x10^4 CFU/ml, respectively.   These results emphasize the necessity for strengthened monitoring and improved application of hygiene and sanitation practices within school canteens. Keywords: Food safety, school children's snacks, school canteen, total microbes